KELAYAKAN PENUNTUN PRAKTIKUM BIOKIMIA BERBASIS KEARIFAN LOKAL DISERTAI LEMBAR KERJA UNTUK MAHASISWA PENDIDIKAN BIOLOGI (Jurnal Pelangi : Research of Education and Development, 2022)
This development research aims to describe the validity and practicality of a biochemistry practicum guide developed using materials that are around students and include student worksheets. The research subjects were students of the Biology Education study program, STKIP PGRI, West Sumatra. This research was conducted using the ADDIE development model. The results showed that the biochemistry practicum guide module which was developed along with this worksheet was very valid and very practical.